An Assessment of the Social Science Research Environment of the Sri Lankan State University System - Fernando, R. L. S.; Hemachandra, D. W. K.; Muthulingam, A (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2018)
Higher education institutions play a vital role in society in varied capacities, and one major contribution amongst it all is conducting research as a part of knowledge creation and dissemination. Social Science Research thereby provides valuable input for policy makers, decision makers and the public, in order to encourage the well-being of the society. Previous studies have highlighted the importance of conducting social science researches to address social issues and improve quality of life. However, the number of research conducted in this discipline in Sri Lanka is not adequate when compared to that of other countries in the region. Hence, this study aims to explore the present status and challenges that hinder the number of social science research conducted by academics in State Universities in Sri Lanka. The study conducted a detailed literature review that was followed by in-depth interviews with 50 academics representing five state universities in Sri Lanka. The universities were selected based on the availability of Social Sciences and Humanities Faculties/Departments. The data were then analysed qualitatively based on the Grounded Theory Method to achievestudy objectives. The study revealed three main categories that limit the number of social science researches conducted in State Universities in Sri Lanka. They are; organizational factors, individual factors, and policy related factors. In addition, collaboration with other universities/ faculties, publication opportunities, research awards, and research allowance were identified as aspects in support of social science research in Sri Lanka. The study findings significantly helps in policy making, to identify the present status as well as factors that can contribute to enhance the level of social science related research among academics of State Universities in Sri Lanka.
Keywords: Research Environment, Social Sciences Research, State Universities